SOCIO-ECONOMIC-ECOLOGICAL EFFECTS OF THE DEVELOPMENT OF MULTIFUNCTIONAL INNOVATIVE AND RECREATIONAL AQUACULTURE CENTERS - Tiutiunnyk, Hanna (Collection of scientific papers «ΛΌГOΣ», 2023)
Innovative and recreational aquaculture centers are specialized multifunctional complexes equipped with innovations that combine elements of aquaculture (breeding of fish, seafood and other aquatic organisms) and recreation (fun games, active recreation, restaurants, hotels, etc.). Innovative recreation centers combine the functions of entertainment, product production, environmental sustainability and new jobs. Thanks to the formation of such centers, there is an opportunity to use natural resources and create new opportunities for the development of the local economy (Fig. 1).